Regulatory framework for credit accounting in digital banks - Jumayeva Gulrux Jo‘raqulovna; Yusupov Otayor Otabekovich (THE INNOVATION ECONOMY, 2026)
This article examines the regulatory and legal foundations of credit accounting in digital banks, mechanisms for managing credit risk, and the impact of modern digital technologies on the banking sector. The study analyses national legislation, international standards (Basel III, EBA guidelines), and global best practices to identify existing challenges in regulating digital lending processes. The findings reveal that the enhancement of regulatory frameworks is essential for improving transparency, information security, and the overall quality of bank credit portfolios.